Measuring Objective and Subjective Intelligibility Using Speech Materials from the Tracking of Noise Tolerance (TNT) Test - Kuk, Francis; Slugocki, Christopher; Korhonen, Petri (Journal of the American Academy of Audiology, 2023)
Background The results of tests measuring objective speech intelligibility are similar to those measuring subjective speech intelligibility using speech materials with minimal context. It is unclear if such is the case with contextual materials.Purpose This article compares objective and subjective intelligibility difference (OSID) between normal hearing (NH) and hearing impaired (HI) listeners in the unaided and aided modes using speech materials adapted from the Tracking of Noise Tolerance (TNT) test.Research Design Single-blind within-subjects design.Study Sample Twenty-four NH and 17 HI older adults.Data Collection and Analysis Listeners completed the objective and subjective intelligibility measures at 75 and 82 dB sound pressure level (SPL) speech input levels. Five signal-to-noise ratios were tested to generate the objective and subjective speech intelligibility performance intensity (P-I) functions. Both NH and HI listeners were tested in the unaided mode. The HI listeners were also tested using their own hearing aids (HAs). Objective and subjective speech reception thresholds at a 50% criterion (SRT50s) were estimated from each individual P-I function. The difference between the objective SRT50 and subjective SRT50 was used to estimate OSID.Results Objective and subjective SRT50s were significantly better in NH than in HI listeners (chi-square(1) = 26.29, p < 0.001) at each speech input level in the unaided mode. However, there was a significant interaction between listener group and intelligibility type (chi-square(1) = 9.43, p = 0.002) where SRT50s were lower for subjective than objective P-I functions only in the HI group. The SRT50s of HI listeners were also affected by hearing mode, where both objective and subjective intelligibility was improved when HI listeners were tested while wearing their own HAs. In general, objective and subjective SRT50s showed moderate-to-strong correlations across most combinations of listener groups and test conditions (r = 0.59–0.86, p < 0.01) except for HI listeners tested with their own HAs (r = 0.39, p = 0.128).Conclusion Similar objective and subjective intelligibility was observed in NH listeners but better subjective intelligibility than objective intelligibility was noted in HI listeners when tested in the unaided and aided modes.
Keywords: subjective intelligibility; objective intelligibility; objective-subjective intelligibility difference (OSID)